PERJUANGAN PEREMPUAN PAPUA DALAM NOVEL NAMAKU TEWERAUT DAN TANAH TABU - Sarip Hidayat (Madah: Jurnal Bahasa dan Sastra, 2017)
Tanah Tabu and Namaku Teweraut tell a story about the condition of Papuan women who are in the shackles of tradition. In the two novels, there is an attempt to struggle his characters to try to get out of an impartial tradition for women. This study aims to discover the similarities and differences between the two novels in terms of structure and how the struggles of the figures are described and give the reason why they did the struggle. Theories used arecomparative literature and gender studies. The method used in this research is descriptiveanalytical method. Based on the analysis and comparison of data, it can be concluded that the two novels studied have similarities of background, characterization, plot, and theme. The difference between the two appears in the element point of view. Based on the theme, it can be concluded further that the struggle of Papuan women in two novels have the same view, that education becomes the way out for Papuan women to get equal degree with men.